Del Antropoceno al Ecoceno: propuestas jurídicas de la transición ecosocial para el cuidado de la vida - Borràs-Pentinat, Susana (Iberoamerican Journal of Development Studies, 2023)
In these times when we experience, first-hand, the limits of our existence, COVID-19 has proved to be another of the multiple consequences of the human footprint on the Earth ecosystem. The destruction of habitats, the extinction of biodiversity, the climatic emergency… have generated a situation of global disease, which places the Earth system at the limits of its capacity and in which humans are not at all oblivious to the consequences of this pathology. The purpose of this article is to reflect on the need to promote an ecosocial transition towards a new eco-civilization, in which the legal paradigm established in the Anthropocene era must necessarily move towards the life system, towards the «Ecocene», a new era in which life is the center and it is articulated through a legal system guided by the welfare and care of all living beings. The conjunction of all eco-legal elements results in the so-called «Earth law», whose main center is the recognition of the pluri-subjectivity and the attribution of rights to all living beings of the Earth ecosystem.